TRANSLATION PROCEDURES IN STARTUP GUIDE SONY XPERIA C5 ULTRA DUAL SMARTPHONE - Siregar, Nurmaliana Sari (Universitas Islam Sumatera Utara (UISU), 2024)
This research aimed to identify the translation procedures employed in the startup guide for the Sony Xperia C5 Ultra Dual Smartphone from English to Indonesian. The ata were collected from the guide and analyzed using a descriptive qualitative method, focusing on established translation procedures. Translation theory categorizes these procedures into seven types: borrowing, calque, literal, transposition, modulation, equivalence, and adaptation. The studies revealed that five of these procedures—literal, adaptation, borrowing, transposition, and modulation—were used in the translation process. The results showed that literal translation was the most frequently applied method, with 19 out of 48 items translated in this way. Adaptation translation accounted for 12 items, while borrowing and transposition were each applied to 8 items. Modulation was the least utilized procedure, appearing in only 1 item. This analysis highlights the predominance of literal and adaptation methods in translating technical documents, emphasizing the importance of accurate and contextually appropriate translations in user guides for electronic devices.